AN INVESTIGATION INTO DOMESTICATION AND FOREIGNIZATION IN THE ENGLISH TRANSLATION OF CULTURE-SPECIFIC ITEMS IN VŨ TRỌNG PHỤNG’S DUMB LUCK NOVEL AND READERS’ PERCEPTION. - Đoàn Thị Ngọc Bích (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Recognizing the importance of culture-specific items (CSIs) in translation, the researcher aims to analyze whether Vietnamese culture-specific items have been translated into English based ondomestication or foreignization. Data were based on culture-specific items taken from “Số Đỏ” novel of Vũ Trọng Phụng and their English equivalents in the Vietnamese version by Nguyễn Nguyệt Cầm and Peter Zinoman. This research also examines readers’ perception of the cultural words. It investigates if readers have difficulties as well as misunderstanding in comprehending culture-specific items in the English translation of “Dumb Luck” novel. To conduct the survey, the questionnaire was designed with 10 domesticated cuture-specific items and 10 foreignized culture-specific items taken from “Dumb Luck” novel to obtain feedbacks from three foreign readers. The findings indicate that the background information plays a significant role in improving the comprehensibility of foreign readers about Vietnamese culture-specific items. The occurrences of foreignizing were much higher than domestication with the domination of literal translation technique. However, the translators should have a parallel combination of both “domestication” and “foreignization” when translating culture-specific items into English. It is essential to provide the background information in order to enhance the effectiveness of English translated Vietnamese masterpieces. At the same time, it is necessary to consider the level of the comprehensiveness to create closeness for foreign readers. Besides, translators should conduct a survey about readers’ perception designed for various foreign audiences so that translated texts are more popular with international friends.